Mammary epithelial cell-derived exosomal miR-155-inhibitor played a key role in the treatment of mastitis via down-regulation of TLRs/NF-κB signaling pathway to inhibit inflammatory response: Exosomal miR155-inhibitor for mastitis - Lu, Jinye; Gu, Beibei; Han, Xinlu; Feng, Yinnan (Cellular and Molecular Biology, 2023)
Mastitis is a common disorder in women capable of altering the normal physiological function of the mammary gland. It has been reported that mammary epithelial cells (MECs) could be involved in treating mastitis by regulating the inflammatory response and miR-155 might participate in this process. However, the effects of MECs-derived exosomal miR-155-inhibitor in treating mastitis and the regarding mechanism are still unknown. In our study, mouse mammary epithelial cells (HC11) were applied to study the role of MECs-derived exosomal miR-155-inhibitor in the treatment of mastitis and explore the mechanism. Results in our study showed that specific markers including CD63 and Apo-A1 were expressed in blank exosomes and exosomes containing miR-155-inhibitor isolated from transfected HC11 cells. Results of immunofluorescence showed that the blank exosomes and exosomes (containing miR-155-inhibitor) labeled with PKH26 were absorbed in HC11 cells. The level of miR-155 was decreased obviously in Engineered exosomes with miR-155-inhibitor and HC11 cells Transfected with exosome containing miR-155-inhibitor. The level of miR-155 was increased and cell apoptosis was promoted obviously in HC11 cells induced by LPS, however, they were decreased obviously after transfecting with an exosome containing miR-155-inhibitor. The level of TLR2, TLR4, TLR6, NF-κB, TNF-α, and IL-1β was increased obviously in LPS-induced HC11 cells, however, they were decreased obviously after transfecting with an exosome containing miR-155-inhibitor. The change in IL-10 level is opposite to the above genes. Taken together, exosomal miR-155-inhibitor could decrease the apoptosis of MECs and inhibit the inflammatory response to treat mastitis by down-regulation in the TLRs/NF-κB signaling pathway, which might be a new therapeutic target for mastitis.